Impact of climate resilient technologies in Chittoor district of Andhra Pradesh - Sreenivasulu, S; Sudhakar, P S; Divya, V; Kumar, T Ramu; Prasad, J V; Meera, Shaik N (Indian Farming, 2024)
Indian agriculture, heavily reliant on monsoons, faces climate sensitivity, with fluctuations in rainfall and temperature significantly impacting crop productivity and threatening food security. Recognizing this challenge, the Indian Council of Agricultural Research (ICAR) launched the National Innovations in Climate Resilient Agriculture (NICRA) programme in 2010-11. NICRA aims to make villages climate-proof by providing site-specific technological demonstrations to enhance farmers’ adaptive capacity in climatically vulnerable districts. Implemented by KVK, Chittoor (RASS), the NICRA project in Chittecherla and Deendarlapalli villages in Andhra Pradesh from 2015 to 2021 focused on enhancing agriculture and allied sectors’ resilience to climate vulnerabilities through improved production and risk management technologies. As part of this initiative, eleven community irrigation tanks in the villages were renovated to improve surface water storage and groundwater recharge, ensuring water availability for crops over a larger area. Recharging 129 bore wells near the tanks by 3 feet benefitted 242 farmers. The adoption of resilient technologies led to notable increases in yield: paddy by 11.5%, groundnut by 15.8-38%, tomato by 11.6-24.5%, and mango by 12.7%. These climate-resilient practices have played a significant role in mitigating the adverse effects of climatic aberrations in the NICRA cluster villages over the years.